Race and the death penalty: the legacy of McCleskey v. Kemp - Keys, David Patrick (Lynne Rienner Publishers, 2016)
Racial bias and capital punishment / Richard C. Dieter -- McCleskey v. Kemp and the reaffirmation of separate but equal / by David Keys and R.J. Maratea -- Revisiting McCleskey v Kemp : a failure of sociological imagination? / Tony G. Poveda -- McCleskey and the lingering problem of race / Ross Kleinstuber -- Overcoming moral peril : how empirical research can affect death penalty debates / R.J. Maratea -- Capital sentencing and structural racism : the source of bias / Gennaro F. Vito and George E. Higgins -- Capital case processing in Georgia after McCleskey : more of the same / Jacqueline Ghislaine Lee, Ray Paternoster, and Michael Rocque -- Addressing contradictions with the social psychology of capital juries and racial bias / Jamie L. Flexon -- Nothing succeeds like failure : race, decision-making, and proportionality in Oklahoma homicide trials, 1973-2010 / David Keys and John F. Galliher -- Why do we need the death penalty? / Robert M. Bohm -- The death penalty's dirty little secret / Franklin E. Zimring -- Race of victim and American capital punishment / Franklin E. Zimring